CONTENT AND LEVEL OF COMPETENCE OF MUSIC CULTURE LESSONS IN SECONDARY SCHOOLS - Nazarov Kholmurod Abdujjaforovic (Journal Park Publishing, 2024)
This article examines and highlights "the content and level of competence of music culture lessons in secondary schools”.
Keywords: Education and training, Music Culture, Art, pedagogy, competency, integration.